Current landscape of Open Educational Resources initiatives by Malaysian academic libraries - Nurul Diana, J.; Noorhidawati A.; Yanti Idaya A.M.K. (Malaysian Journal of Library and Information Science, 2024)
The contribution of librarians to open educational resources (OER) is increasingly influenced by the open science and open data movements. However, their involvement in OER initiatives remains limited, primarily focusing on managing learning resources and providing information literacy training to facilitate access to OER. This study delves into the role of libraries in adopting OER within their institutions, aiming to explore the current landscape of OER initiatives led by Malaysian academic libraries and the challenges faced by academic librarians, guided by the CARE Framework. Through interviews with nine academic librarians, the study examines the current state of OER initiatives, and the obstacles librarians encounter in supporting these efforts. Findings indicate that Malaysian academic libraries are committed to supporting OER through the creation of library guides that enhance user awareness on how to locate and utilise OER resources. Despite the positive opportunities presented by OER, academic librarians face significant challenges, particularly in promoting access and usage. This study offers valuable insights and practical guidelines for academic libraries to enhance their OER services. The conclusions drawn will also aid in future professional development, contributing to the success and sustainability of the OER movement in promoting open education.